SPECIFIC FEATURES OF TITLES OF FILMS (TAMADDUN NURI JURNALI, 2025)
The article deals with the titles of popular English films, which are considered as the object of a great number of scientific researches. Onomastics is the branch of linguistics dealing with proper nouns, common nouns and titles of films as well. One of the most important functions of titles of movies is a fuctional one.